PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING PADA TEMA 5 KELAS V DI UPTD SD MANERON 3 KECAMATAN SEPULU - Maimuna, Siti; Ida Mardiayana, Isna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objectives of this development research are (1) to determine the validity of developing e-modules based on discovery learning, (2) to determine the effectiveness of developing e-modules based on discovery learning and (3) to determine the attractiveness of developing e-modules based on discovery learning. Development research uses the 4D Define, Design, Develop and Disseminate model. Based on the results of the research that has been carried out, first the results obtained from the validity were tested on 90% validators of teaching material experts, 93.75% of material experts, 75% of language experts and 90% of learning design experts. The average data validity results from expert validators obtained a percentage of 87.18%, which was categorized as very valid for use. The results of the effectiveness of e-module teaching materials are measured from learning outcomes tests and learning implementation. The results of the learning test for class V students obtained classical completeness of 100% which was categorized as complete criteria. Then for the implementation of the first learning, the score was 91.66%, for the implementation of the second learning, it was 95.34% with the criteria for learning being implemented. The attractiveness of the module teaching materials is measured from teacher response questionnaires and student response questionnaires. The average percentage of teacher and student response questionnaires obtained was 92.04%, which was stated to be very interesting to use. Based on the results of research that has been carried out, the development of e-modules based on discovery learning in theme 5 in class V is stated to be very valid, effective and interesting to use in the learning process